Right to health care services in view of discussion on legalization of soft drugs - Kmieciak, Błażej (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
Patientsʼ rights are a regular part of debates on health care. For many years the issue of respect for dignity and intimacy of patients has aroused a big interest. Also the issue of the development of biology and medicine is associated with problems of patientsʼ rights. Does scientific progress cause (automatically) patient’s entitlement to new services? A similar question has become topical in the context of a discussion on therapeutic marijuana. In the media discussion there have been reports indicating that marijuana has significant medicinal properties. Some scientists also share a similar view. On the other hand, it is indicated that effects of the drug are not well recognised. Moreover, it is added that only some of the ingredients of marijuana may act therapeutically. How, however, a similar situation can be shown from the perspective of respect for the patient ʼs right to health care services corresponding to the current state of medical knowledge? Can the lack of access to legal marijuana violate the right in question? Perhaps, in a similar situation the patient’s right to dignity is also violated. Is the “medical marijuana” still a drug?